International Financial Statistics, August 2016. (International Financial Statistics; International Financial Statistics, 2016)
The August 2016 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. IFS, Balance-of-Payments Statistics, Direction of Trade Statistics, and Government Finance Statistics are available on CD-ROM by annual subscription. Quarterly issues of this publication provide, for 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. IFS contains country tables for most members, as well as for Anguilla, Aruba, the Central African Economic and Monetary Community, Curacao, the currency union of Curacao and Sint Maarten, the Eastern Caribbean Currency Union, the euro area, Montserrat, the former Netherlands Antilles, Sint Maarten, the West African Economic Monetary Union, West Bank and Gaza, and some non-sovereign territorial entities for which statistics are provided internationally on a separate basis. Also, selected series are drawn from the country tables and published in area and world tables.